Service Quality Perceptions, Online Visibility, and Business Performance in Rural Lodging Establishments. (February 2017) - Melo, António J.D.V.T.; Hernández-Maestro, Rosa M.; Muñoz-Gallego, Pablo A.
In the tourism industry, most customer feedback and searches for relevant information take place online. Therefore, it is important to improve understanding of the business consequences of both customers' online comments and businesses' online visibility. For this study, the authors collected comments and visibility data (advertising expenditures) from a leading rural tourism infomediary website, related to 408 French rural lodging establishments. A complementary survey provided information about the lodging establishments' performance (reputation and profitability). The results reveal that tourists' positive perceptions of global service quality, as reflected in their comments, depend on their dual perceptions of the lodging and the surroundings. In turn, positive global service quality perceptions and visibility on an infomediary website positively affect business performance. These findings have implications for tourism scholars, as well as for establishment owners trying to track the factors that affect tourists' evaluations of their service provision.